Morphological and Habitat Characteristics of Asparagus (Asparagus officinalis L.) and Socio-Economic Structure of Producers - Açıkgöz Altunel, TayyiÌ‡be (Turkish Science and Technology Publishing (TURSTEP), 2021)
Asparagus officinalis L. (Asparagus) is a species that belongs to Liliaceae family, 300 species grow naturally on earth and 12 species of it grow naturally in Turkey. Generally, above-soil and under-soil parts of some of its different species are used as a diuretic, tonic, heart sedative, demulsan, antidiarrheal, antidisenteric, galactagogue, aphrodisiac, antispasmodic in traditional treatment. In addition to that it is also consumed as a food. To date various pharmacological studies were conducted on many types of that species. However, no comprehensive study has been made on Asparagus species, including anatomical, morphological habitat and productive characteristics. In this study, morphological features of Asparagus as a medical aromatic plant in spreading areas, its raising environment features, economy, socio-economic status of producers, and contributions of its production on both household and local economy have been examined based on Kastamonu case. As a result, Kastamonu district has wide range with respect to climate, which helps Asparagus plant being cultivated in appropriate growing environments, having potential to provide opportunity to generate high earnings. But producers do not have adequate expertise to cultivate and grow it, lack of any relevant training/education, so efficiency is low and it does not have the value it deserves.
Keywords: kastamonu; S; Agriculture (General); habitat; Agriculture; S1-972; asparagus; morphology; rural development; 2. Zero hunger; 15. Life on land; 6. Clean water